Habitat use and conservation status of birds from El Paraíso wetland, Lima, Peru - Fe de errata - Quiñonez, Alessandra S. (2017)
Error in: Quiñonez A.S., F. Hernandez. 2017. Uso de hábitat y estado de con-servación de las aves en el humedal El Paraíso, Lima, Perú. Revista peruana de biología 24(2): 175 - 186 (Julio 2017). doi: http://dx.doi.org/10.15381/rpb.v24i2.13494 Must be considered corrections in typographical error of quotations, one erroneously separated paragraph, and one reference.